(untitled) (International Journal of Food and Nutritional Sciences, 2022)
This paper explores how women’s identity crisis are complexly portrayed in the writings of two well-known authors, Meena Kandasamy and Fatima Bhutto. It examines the complex difficulties faced by female characters in negotiating societal expectations, cultural constraints, and the quest for selfhood through a close analysis of Fatima Bhutto’s The Runaways and Meena Kandasamy’s When I Hit You: Or, A Portrait of the Writer as a Young Wife